PERANCANGAN SISTEM INFORMASI PELAYANAN ADMINISTRASI PENDUDUK PADA KELURAHAN LEMBANGSARI - Tuti Sudaryanti (Journal of Innovation And Future Technology (IFTECH), 2024)
The smallest government agency at village level is the sub-district office, which is an agency that processes population data, especially in the process of making Family Cards (KK), Birth Certificates, Death Certificates, Immigrant Certificates and Moving Certificates. To be able to improve population data collection and its reports to higher agencies, namely sub-districts, steps are needed to develop a data management system. The aim of this research is to analyze the running system and design a computerized information system. The data collection methods used in this research are direct observation, interviews, literature, and analysis methods and system design using UML. The administrative service system in Lembangsari sub-district still uses ledgers to input data for letters that have been created. Searching for the letter file to be created is still experiencing difficulties due to the accumulation of files. Mail files that have been created are prone to being lost. Therefore, a follow-up information system that utilizes information technology will help collect data on the population of a sub-district, especially in the process of collecting population data, Family Cards (KK), Birth Certificates, Death Certificates, Immigrant Certificates and Moving Certificates to be more effective and efficient.